ASSISTING OF NUANSA GEMBIRA COFFEE PRODUCTS TOWARDS HALAL CERTIFICATIONS WITH THE SI-HALAL APPLICATION IN DELES VILLAGE, BATANG DISTRICT, CENTRAL JAVA - Afiati, Lely; Verawati, Liesta; Anwar, Muhamad (Jurnal Layanan Masyarakat (Journal of Public Services), 2024)
A halal certificate is a legal requirement that must be fulfilled for every Micro, Small, and Medium Enterprise. Kopi Nuansa Gembira is a pure, original ground coffee business without any mixtures which still does not have halal certification. The problems faced will result in distrust and sales volumes that continue to decline if this is still ignored. This service is carried out to help Nuansa Gembira Coffee to obtain a halal certificate. The lack of understanding regarding halal products makes it necessary to provide assistance and knowledge to Kopi Nuansa Gembira. The solution offered is in the form of aid related to halal certificates and obtaining halal certificates. The stages of halal product assistance are: The preparation stage is surveying the service location to explore the problems faced by Nuansa Gembira coffee. Phase 1, the service team and the owner of Nuansa Gembira Coffee went to the Ministry of Religion office to consult regarding halal products. Stage 2 prepares all the necessary documents. 4. Sustainability Phase of issuing a halal certificate for Kopi Nuansa Gembira. The assistance results will start from January 2023, namely when the initial assistance starts from preparations for verifying problems with partners to convincing the owner of Kopi Nuansa Gembira to apply for halal certification through the halal application. The business actor then fills it out and submits it after filing and filling in the complete documents. After going through all the processes, including the verification, validation, and return processes, both by the companion and by BPJPH, on June 9, 2023, the halal certificate for Kopi Nuansa Gembira was issued.